2006
DOI: 10.1590/s0100-736x2006000200010
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologia, sinais clínicos e distribuição das lesões encefálicas em bovinos afetados por meningoencefalite por herpesvírus bovino-5

Abstract: Seven outbreaks and an isolated case of meningoencephalitis caused by bovine herpesvirus-5 (BoHV-5) in cattle in Rio Grande do Sul, Brazil, occurring in 2002-2004, are described. From a total population at risk of 1,359 cattle, 54 1-18-month-old calves from both sexes and several breeds were affected and 50 died spontaneously or were euthanatized while moribund. The highest frequency of cases was in recently weaned calves or calves submitted to other stressing factors. General rates of morbidity, mortality and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
30
2
62

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(107 citation statements)
references
References 23 publications
(42 reference statements)
11
30
2
62
Order By: Relevance
“…Edema was the most common finding, corroborating with others studies where the authors suggested that edema could contribute to the development of malacia due to ischemia (Rissi et al 2006, Rissi et al 2008.…”
Section: Fig2 Adjusted Geometric Means* Of Lesions Distributed By Asupporting
confidence: 89%
See 3 more Smart Citations
“…Edema was the most common finding, corroborating with others studies where the authors suggested that edema could contribute to the development of malacia due to ischemia (Rissi et al 2006, Rissi et al 2008.…”
Section: Fig2 Adjusted Geometric Means* Of Lesions Distributed By Asupporting
confidence: 89%
“…Region 1 included the olfactory bulb and telencephalon; region 2 included the basal nucleus, thalamus, midbrain, pons, and medulla oblongata. et al , Elias et al 2004, Rissi et al 2006, Ferrari et al 2007, Rissi et al 2008. The absence of lesions in the cervical spinal cord, cerebellum, and Gasserian ganglia has been previously reported (Rissi et al 2008).…”
Section: Fig2 Adjusted Geometric Means* Of Lesions Distributed By Amentioning
confidence: 80%
See 2 more Smart Citations
“…Respecto a los diagnósticos diferenciales en los casos negativos y con base en alteraciones histopatológicas observadas en la coloración de rutina Hematoxilina-Eosina (H&E) de los tejidos evaluados, se consideró en algunos casos, compatibilidad con la meningoencefalitis causada por el Herpes Virus Bovino 5 (BoHV-5), agente recientemente descrito en Colombia (14), siendo que estos casos mostraron, gliosis, manguitos perivasculares, malacia y células gitter, considerados característicos de este tipo de infección (15). Es importante no dejar de lado otras causas de meningitis inespecíficas, como las de origen bacterial (por Listeria spp), envenenamiento por consumo de plantas tóxicas, intoxicación por plomo, polioencefalomalacia por deficiencia de tiamina y botulismo entre otros (16,17).…”
Section: Discussionunclassified